Internalisasi Nilai-Nilai Etika Perspektif Ibnu Jama’ah dalam Kitab Tadzkirat al-Sami’ wa al-Mutakallim - Sopiyan Hadi; Achmad Affandy (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
Modern higher education faces significant challenges regarding character crisis and moral degradation amidst mass digitalization. This study aims to analyze the mechanism of internalizing ethical values from Ibn Jama’ah's book Tadzkirat al-Sāmi‘ wa al-Mutakallim among STIT Riyadhussholihiin students as a response to contemporary moral issues]. The research employs a qualitative descriptive-analytical approach, combining field research and library research through content analysis, observation, and in-depth interviews. The findings reveal that the internalization process occurs systematically through stages of value transformation, transaction, and transinternalization. Key ethical values internalized include soul purification (tazkiyatun nafs), sincerity of intention, time management, and adab toward educators. The success of this internalization relies heavily on the synergy between students' intrinsic awareness, lecturers' role modeling (uswah hasanah), and a conducive campus ecosystem. The implication of this study is the provision of a practical strategy for Islamic higher education institutions to produce graduates who are khair al-barīyah—individuals who possess broad knowledge, fear of Allah, and leadership integrity.